Barrier properties of natural clay minerals - Дудар, Т.В.; Бугера, С.П.; Кадошніков, В.М.; Злобенко, Б.П. (Proceedings of National Aviation University (archive), 2009)
Clay minerals is a perfect material for geochemical barrier due to their high water resistivity, plasticity, high sorbing capacity, well developed surface and cheapness in extraction and processing. This work studies the peculiarities of uranium sorbtion on clay minerals on the example of bentonite and palygorskite clay from Cherkassy deposit, and clay usage as a barrier material.